2014
DOI: 10.1038/pr.2014.88
|View full text |Cite
|
Sign up to set email alerts
|

Association study of childhood obesity with eight genetic variants recently identified by genome-wide association studies

Abstract: Background:Being overweight or obese is becoming increasingly common in low-and middle-income countries. The present study aimed to examine association of eight genetic variants with obesity and to estimate the cumulative effects of these variants in Chinese children. Methods:We conducted the case-control study in a total of 2,030 subjects. Genotyping of seven novel variants was performed with matrix-assisted laser desorption ionization time of flight mass spectrometry, while rs9939609 was genotyped with tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Genotyping of the three SNPs were carried out with the matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS, Sequenom). The detailed genotyping process has been described previously [19,20]. The call rates of the three SNPs were more than 99.9%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genotyping of the three SNPs were carried out with the matrix-assisted laser desorption ionization time of flight mass spectrometry (MALDI-TOF MS, Sequenom). The detailed genotyping process has been described previously [19,20]. The call rates of the three SNPs were more than 99.9%.…”
Section: Methodsmentioning
confidence: 99%
“…Many replication studies for these loci have been conducted in multiple ethnic populations, including Chinese [15,16,17,18,19,20]. Two recently published studies by Wang et al [19] and Meng et al [20] from our research group confirmed some loci identified by GWA studies to be associated with obesity in Chinese children, and identified ethnic difference of effect size for some loci (supplemental table 1, available at http://content.karger.com/ProdukteDB/produkte.asp?doi=471487 ). …”
Section: Introductionmentioning
confidence: 99%
“…As described before [14], the CPOOA subjects were recruited from children aged 7–18 years old in 5 elementary and middle schools of Haidian District of Beijing, comprising 637 overweight or obese children and 456 normal-weight children. All the obese individuals in the selected schools were recruited with their voluntary participation.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the built environment factors, other factors, including parental excessive BMI, family income, being male, and barbeque food consumption, were found associated with young adolescents' excessive body weight, which were consistent with previous ndings. 12,[32][33][34] For example, genetic factors in uenced fat distribution as well as daily energy expenditure, energy intake, and habitual physical activities. 12 It is also speculated that families with higher incomes could have more access to healthy food and live healthier lifestyles.…”
Section: Mendenhall Argued That Macro-level Political Elements Would mentioning
confidence: 99%